Restriction of burial rites during the COVID-19 pandemic: An African liturgical and missional challenge - Khosa-Nkatini, Hundzukani P. (HTS teologiese studies, 2021)
Burial rites are very common among many Africa communities. In the African context, burials are not the end of life but rather the beginning of another life in the land of the ancestors. In spite of the importance of the African funeral rites, the missional role of the church in mourning and the burial of the dead in the African communities, the COVID-19 pandemic led protocols and restrictions placed a huge challenge on the African religious and cultural practices.Contribution: In the light of the above-named challenges, the article discusses the religious-cultural effect of the pandemic with special focus on the African liturgical and missiological challenges in the context of the COVID-19 restrictions on funerals and burial rites.